The Effect of BMI, Age, Gender, and Pubertal Stage on Bone Turnover Markers in Chinese Children and Adolescents - Cao, Bingyan; Liu, Meijuan; Luo, Qipeng; Wang, Qiao; Liu, Min; Liang, Xuejun; Wu, Di; Li, Wenjing; Su, Chang; Chen, Jiajia; Gong, Chunxiu (Frontiers in Endocrinology, 2022)
Objectives: To ascertain the associations of serum bone turnover markers (BTMs) levels with body mass index (BMI) in Chinese children and adolescents, and whether the influence of BMI, age, pubertal stage on BTMs varied by gender. Methods: A total of 500 students (180 controls and 320 children and adolescents with overweight/obesity) aged 9–14 years were randomly selected from the Chinese National Survey on Students Constitution and Health Cohort. Serum levels of BTMs, including bone formation marker bone alkaline phosphatase (BAP), collagen type 1 C-terminal propeptide (CICP), and bone resorption markers C-terminal telopeptide of type-I collagen (CTX) were determined by commercial enzyme-linked immunosorbent assay kits. The associations among BMI, age, gender, pubertal stage, and BTMs were analyzed. Results: Serum levels of CICP and CTX in overweight/obese children and adolescents were lower than those in controls (p<0.05). Moreover, after subgroup analysis stratified by gender, the decreased serum CICP and CTX levels in overweight/obese children and adolescents were observed only in boys (p<0.05). After adjustment of age and pubertal stage, there was a negative correlation between serum BAP and BMI in both boys and girls (p<0.05). However, the correlations between serum CICP, CTX levels, and BMI were significant in boys but not in girls. Serum BAP and CICP levels were independently correlated with BMI, age, gender, and pubertal stage, while CTX levels were independently correlated with BMI, age, and gender (p<0.05). BAP, CICP, and CTX levels showed a clear age, gender, and pubertal stage dependence with significantly higher values in boys (p<0.05). Conclusions: Our findings support the associations between serum BTMs levels and BMI in Chinese children and adolescents, and suggest age, gender, and pubertal stage differences in this relationship that warrant future studies.